The Digital Turn in Ḥadīth Studies: Ethical Foundations and Strategic Directions - Akbar, M. Alhafidh; Wahid, Abd; Yasin, Taslim HM (Prodi Ilmu Hadis Fakultas Ushuluddin dan Filsafat UIN Ar-Raniry Banda Aceh, 2025)
This article examines the ethical foundations and strategic directions that characterize the ongoing digital turn in ḥadīth studies. As the second principal source of Islamic teachings, ḥadīth is undergoing a profound transformation in how it is accessed, transmitted, and interpreted through digital technologies—particularly mobile applications, online repositories, and social media. While these developments have expanded access and public engagement, they have also raised pressing concerns about authenticity, epistemological disruption, and the marginalization of traditional scholarly authority. Using a narrative literature review approach, the study draws on academic works and digital platforms published between 2014 and 2024 to analyze how Islamic scholars and institutions are responding to these shifts. The findings reveal that digital tools—such as Lidwa Pusaka, Maktabah Syamilah, Jawāmiʿ al-Kalim, and the Digital Islamic Library—have broadened access to canonical texts and enhanced educational outreach. However, the viral circulation of unverified narrations, the influence of algorithm-driven visibility, and the rise of unqualified digital preachers have contributed to the fragmentation and trivialization of prophetic traditions. This article argues that sustaining the integrity of ḥadīth studies in the digital age requires a balanced integration of Islamic ethical principles (akhlāq), critical digital literacy, and strategic scholarly engagement. By grounding innovation in ethical responsibility and reasserting scholarly authority, digital platforms can become effective instruments for preserving the authenticity, relevance, and transformative potential of ḥadīth in contemporary Muslim life.